Proliferation of weapons of mass destruction in the Middle East : directions and policy options in the new century - Russell, James A. (James Avery), 1958- (Initiatives in strategic studies--issues and policies., 2006)
The proliferation of weapons of mass destruction (WMD) is a major concern and the Middle East is at the forefront of U.S.-led efforts to counter and control their spread. This vital book examines specific countries and the interplay among political, economic, cultural and regional factors driving decisions whether to acquire WMD. The result is enhanced understanding of the challenge proliferation poses to U.S. strategy and policy and to the wider international community.